THERAPEUTICAL PURPOSE OF MEDICINAL PLANT AND LOCAL HERBAL PRACTITIONERS BY PITAGUARY’S COMMUNITY FROM MARACANAÚ/CE - Nonato, Dayane Terra Tenório Nonato; Cintia Laurindo Porto, Andrea; Holanda, Eloisa de Alencar; Mendes, Mirian Cézar; da Silva, Anna Paula Sousa; Campelo, Isabella Lima Barbosa; da Silva Pantoja, Patricia (Cadernos ESP, 2023)
The therapeutic use of plants throughout history has been based on the intuitive and speculative knowledge of men and women, who, over time, learned to differentiate the beneficial herbs from those toxic to health. This study aimed understand the influence of the medicinal plants in therapeutic treatment in a indigenous community in Maracanaú-CE. An observational and descriptive case with the Pitaguary indigenous group, in the use of natural plants as medicinal treatment, in Maracanaú-CE. The interviews occurred on 09-11/2017 with the use of a questionnaire adapted from the SATIS-BR scale. Our results showed 25 types of medicinal plants used by Pitaguary’s communities and 15 kinds of association among natural products useful to treat diverse physiological disorders. The article shows the importance of knowing the treatment with natural products and the influence on traditional treatment.